2017
DOI: 10.18632/oncotarget.20620
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognosis of Guillain-Barré syndrome not determined by treatment options?

Abstract: BackgroundThe long-term follow-up system for Guillain-Barré syndrome (GBS) is not well established worldwide. In our study, the preliminary data of the long-term prognosis of GBS are collected to explore the prognosis of GBS and the effect of intravenous immunoglobulin (IVIg) treatment.MethodsThe follow-up data of 186 patients with GBS admitted from 2003 to 2013 were collected in 2015 via phone interview. The GBS disability scale score was ranked by clinician to evaluate the long-term prognosis. The clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…This is supported by evidence from a systematic review of randomized controlled trials showing that early administration of IVIg or PEX significantly hastened recovery from GBS, 24 whereas the evidence for corticosteroids and other agents is limited and of low quality 25 . There is little evidence for long‐term benefits from immunotherapy 26 …”
Section: Discussionmentioning
confidence: 99%
“…This is supported by evidence from a systematic review of randomized controlled trials showing that early administration of IVIg or PEX significantly hastened recovery from GBS, 24 whereas the evidence for corticosteroids and other agents is limited and of low quality 25 . There is little evidence for long‐term benefits from immunotherapy 26 …”
Section: Discussionmentioning
confidence: 99%
“…There is no study showing that a second IVIG application is effective when deterioration continues in GBS (2). It has been reported in the literature that treatment options in GBS prognosis are not effective and that recovery may be due to self-limitation of the disease (23). In our study, 44 patients (86.3%) received IVIG and six patients (11.8%) underwent plasmapheresis+IVIG.…”
Section: Discussionmentioning
confidence: 64%
“…It was reported that by the third month, 47.1% of GBS patients are expected to have a complete recovery, while 24.3% will have poor recovery (wheelchair-bound) 40. One longitudinal study stated that the rates of GBS patients with complete recovery or minor limitations was 41% in the first month, 71% in the third, 86% in the sixth, and 92% in the twelfth 41. Residual paralysis at the second month post onset of disease was highly associated with patients of age 8–14 years (65.2%) in this setting, which is compatible with findings reported by a study conducted in Iraq 12.…”
Section: Discussionmentioning
confidence: 99%